Individual asymmetry as a predictor of fitness in the bat Carollia perspicillata. (15th September 2019) - Monteiro, Leandro R.; Mellado, Breno; Nogueira, Marcelo R.; de Morais‐Jr, Marcio M.
Abstract: The measurement of fitness in wild populations is a challenging task, and a number of proxies have been proposed with different degrees of success. Developmental instability/stability (DI) is an organismal property associated with variance in bilateral asymmetry (fluctuating asymmetry—FA) and a correlated effect on fitness. This study provides evidence to corroborate the hypothesis that asymmetry partly reflects DI and is correlated with a reduction in fitness measured by survival and reproduction in bats. We studied two colonies of the bat Carollia perspicillata in southeastern Brazil over 5 years, marking and recapturing individuals. Gaussian mixture models for signed Forearm Asymmetry (ForA) distribution indicated that ~20% of asymmetry variation was due to DI heterogeneity among individuals. ForA, body condition (Scaled Mass Index—SMI) and Forearm Length (ForL) were used as predictors of survival probability in Cormack‐Jolly‐Seber models. Asymmetry was negatively associated with survival, whereas SMI and ForL were positively associated. The male C. perspicillata defend sites within the roost that are favoured by female harems, but there are mating opportunities for bachelor males, leading to both territorial disputes and sperm competition. As predicted by sexual selection, ForA was negatively associated with relative Testicle Length, a measure of reproductive potential. In females, ForA was negatively associated with the probability of two pregnancies (as opposed to one) in a given breeding season. The effect magnitudes and directions of associations suggest that asymmetry, even though not perfectly reflecting DI variation, is a useful predictor for fitness components in C. perspicillata . Abstract : Left: group of C. perspicillata females (Harem). Right: estimated decrease in survival probability with increasing Forearm Asymmetry.